1986
DOI: 10.1542/peds.78.1.44
|View full text |Cite
|
Sign up to set email alerts
|

Absent Hypoxic and Hypercapneic Arousal Responses in Children With Myelomeningocele and Apnea

Abstract: Hypoxic and hypercapneic arousal responses from quiet sleep were tested in seven infants with myelomeningocele and Arnold-Chiari malformation who were symptomatic with apnea and/or hypoventilation. All infants with myelomeningocele required tracheostomy and posterior fossa decompression. Responses were compared with those of nine healthy control infants. To assess hypoxic arousal, inspired Po2 was decreased until the end-tidal (alveolar) Po2 reached 45 mm Hg for a maximum of three minutes. Eleven studies were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The increased risk of SDB in patients with MMC is a consequence of the abnormalities in the spinal cord, brainstem function, pulmonary function, and upper airway maintenance that are commonly appreciated in this patient population. 33 , 34 , 36 , 38 , 39 In fact, commonly associated neurological conditions like CM-II and hydrocephalus are known to affect respiratory pattern and reflex response while sleeping, leading to SDB. 32 , 40 Abnormalities of the brainstem and respiratory centers may serve as the mechanism involved in producing central apnea, whereas compression of the nuclei of cranial nerves IX and X may result in upper airway obstruction due to decreased ability to maintain upper airway patency 41 MMC with CM-II results in abnormal brainstem control resulting in absent arousal responses to hypoxia and hypercapnia, and absent ventilatory responses to hypoxia and hypercapnia in these patients ( Figure 1 ).…”
Section: Sleep-disordered Breathing In the Child With Spina Bifidamentioning
confidence: 99%
See 4 more Smart Citations
“…The increased risk of SDB in patients with MMC is a consequence of the abnormalities in the spinal cord, brainstem function, pulmonary function, and upper airway maintenance that are commonly appreciated in this patient population. 33 , 34 , 36 , 38 , 39 In fact, commonly associated neurological conditions like CM-II and hydrocephalus are known to affect respiratory pattern and reflex response while sleeping, leading to SDB. 32 , 40 Abnormalities of the brainstem and respiratory centers may serve as the mechanism involved in producing central apnea, whereas compression of the nuclei of cranial nerves IX and X may result in upper airway obstruction due to decreased ability to maintain upper airway patency 41 MMC with CM-II results in abnormal brainstem control resulting in absent arousal responses to hypoxia and hypercapnia, and absent ventilatory responses to hypoxia and hypercapnia in these patients ( Figure 1 ).…”
Section: Sleep-disordered Breathing In the Child With Spina Bifidamentioning
confidence: 99%
“…Several studies have reported a higher prevalence of SDB in patients with MMC and CM-II by evaluating patients with the signs or symptoms suggestive of respiratory abnormalities, 36 , 39 , 53 or after retrospectively evaluating patients with MMC based on having any previously completed polysomnography. 32 Despite these findings, no clear predictors of SDB have been identified in patients with MMC and CM-II.…”
Section: Sleep-disordered Breathing In the Child With Spina Bifidamentioning
confidence: 99%
See 3 more Smart Citations